The relationship between terrain and rural migration (1965–2013) on the north of Turkey (the case of Kastamonu) - Erkan Buğday, Seda; Özden, Sezgin (Springer Science and Business Media LLC, 2017)
Migration is one of the most important issues in Turkey today. Notably, the state forest enterprises are affected by the social, economic, and ecological dimensions of migration; these enterprises find it increasingly difficult to find labor to operate effectively in the forestry activities with each passing day. This study examined population movement over the 1965-2013 period in Kastamonu forest villages to assess how topographical factors affected this movement. Kastamonu is the province in which most of Turkey's forest products are produced, and 99% of the province's rural population consists of forest villagers. This study investigated population fluctuations of 883 villages within and 137 villages adjacent to these forests and found a negative linear tendency in these populations. The purpose of this study is to identify a relationship between the decreasing population and the terrain of the forest villages (including aspect, slope, elevation, and distance to the provincial and district centers) using spatial, simple, and partial correlation analyses. The statistical analysis revealed a negative and significant relationship between population decrease and terrain. As a result, without taking the other reasons for migration into account, the tendency of the rural migration was determined to increase as the slope, elevation, and distance to the province centers increased. The basis for a predictive model of forest villagers' migration might thus be created by this study. Also, the driving force of migration might be revealed through quantitative modeling, and this might help create more rational development plans and programs.
Keywords: Rural Population; Ecology; Turkey; Population Dynamics; Forestry; Management, Monitoring, Policy and Law; Forests; Pollution; Article; Environmental Science(all); Humans; Social Planning; Developing Countries; Demography; Environmental Monitoring; 1. No poverty; 15. Life on land; 13. Climate action; 11. Sustainability